2016
DOI: 10.1177/0960327116677355
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of curcumin against mercury-induced hepatic injuries in rats, involvement of oxidative stress antagonism, and Nrf2-ARE pathway activation

Abstract: Mercury (Hg) represents a ubiquitous environmental heavy metal that could lead to severe toxic effects in a variety of organs usually at a low level. The present study focused on the liver oxidative stress, one of the most important roles playing in Hg hepatotoxicity, by evaluation of different concentrations of mercuric chloride (HgCl2) administration. Moreover, the protective potential of curcumin against Hg hepatotoxic effects was also investigated. Eighty-four rats were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 59 publications
(68 reference statements)
1
25
0
Order By: Relevance
“…Several reports have also recognized the protective capacity of curcumin on liver injury produced by some xenobiotics. Curcumin (100 or 200 mg/kg/day intra peritoneal) has been previously described to exhibit a significant hepatoprotective activity against liver damages induced by aflatoxin B1 [ 96 ], lambda cyhalothrin [ 97 ], CCl 4 [ 98 , 99 ], mercury [ 100 ] and other heavy metals [ 101 ] in adult rats. Levels of lipid peroxidation, serum biomarker enzymes, liver MDA, hydroxyproline and liver antioxidants (i.e., GSH, SOD, catalase) were correspondingly modified after curcumin treatment.…”
Section: Cellular and Molecular Mechanisms Of Curcumin In The Prevmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have also recognized the protective capacity of curcumin on liver injury produced by some xenobiotics. Curcumin (100 or 200 mg/kg/day intra peritoneal) has been previously described to exhibit a significant hepatoprotective activity against liver damages induced by aflatoxin B1 [ 96 ], lambda cyhalothrin [ 97 ], CCl 4 [ 98 , 99 ], mercury [ 100 ] and other heavy metals [ 101 ] in adult rats. Levels of lipid peroxidation, serum biomarker enzymes, liver MDA, hydroxyproline and liver antioxidants (i.e., GSH, SOD, catalase) were correspondingly modified after curcumin treatment.…”
Section: Cellular and Molecular Mechanisms Of Curcumin In The Prevmentioning
confidence: 99%
“…Regarding protective ability of curcumin against heavy-metals (such as copper, cadmium, chromium, mercury, lead and arsenic), its free radical scavenging/reducing power/chelating capacities can restrain the heavy-metals-promoted hepatotoxicity by liver oxidative stress-related antagonism. These abilities were connected with the induction of the Nrf2/antioxidant response elements/Kelch-like ECH associated protein 1 (Nrf2/ARE/Keap1) pathway [ 100 , 101 ]. On the other hand, curcumin also exhibited a dose-dependent protection in CCl 4 -induced liver damage of Jian carp ( Cyprinus carpio var.…”
Section: Cellular and Molecular Mechanisms Of Curcumin In The Prevmentioning
confidence: 99%
“…A study on kidney ischemia/reperfusion model showed that Mn(III) meso-tetrakis(N-n-hexylpyridinium-2-yl)porphyrin contributed to the upregulation of numerous endogenous antioxidant defenses that are, at least in part, controlled by Nrf2 (14). Such scenario was reportedly operative with redox-active curcumin, nitroxides, and flavonoids (22,26,31,39,44,63).…”
Section: Redox Properties Of Mn Complexes Control Their Anticancer Efmentioning
confidence: 99%
“…There is a protective effect conferred by the AO in Cd-induced OS and cardiovascular dysfunction 26 . A beneficial influence occurred with curcumin against Hg-induced OS in the liver 27 . The effect is attributed to free radical scavenging.…”
Section: Curcuminmentioning
confidence: 91%